California Women Lawyers Annual Dinner in San Diego - Watkins, Howard::::::::: (1989)
Hon. ? (wearing green jacket) swearing-in California Women Lawyers 1989-90 officers: ?, Grace Emery, ? Doris Coleman, ? and ?